2011
DOI: 10.1111/j.1460-9568.2011.07659.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dopaminergic neurons in organotypic mesencephalic-striatal co-cultures - evidence for a facilitatory effect of dopamine on the glutamatergic input mediated by α-1 adrenergic receptors

Abstract: Organotypic cultures (OCs) have been widely used to investigate the midbrain dopaminergic system, but only a few studies focused on the functional properties of dopaminergic neurons and their synaptic inputs from dopaminergic and non-dopaminergic neurons also contained in such cultures. In addition, it is not clear whether the culturing process affects the intrinsic neuronal properties and the expression of specific receptors and transporters. We performed patch-clamp recordings from dopaminergic neurons in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
(104 reference statements)
2
6
0
Order By: Relevance
“…Therefore, α1-AR actions on DA neuron excitability follow synaptic activation induced by action potentials from presynaptic neurons. In accordance with our results, Cucchiaroni et al,(2011) reported that α1-AR activation increases glutamate release onto DA cells of mesencephalic-striatal co-cultures. The enhanced glutamate release was dependent on presynaptic action potentials and had no effect on the sensitivity of postsynaptic glutamate receptors in DA cells.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, α1-AR actions on DA neuron excitability follow synaptic activation induced by action potentials from presynaptic neurons. In accordance with our results, Cucchiaroni et al,(2011) reported that α1-AR activation increases glutamate release onto DA cells of mesencephalic-striatal co-cultures. The enhanced glutamate release was dependent on presynaptic action potentials and had no effect on the sensitivity of postsynaptic glutamate receptors in DA cells.…”
Section: Discussionsupporting
confidence: 93%
“…Gruol and co-workers [39] reported that cells with little electrical activity had low resting [Ca 2+ ] i levels (∼50 nM); this may be consistent with our changes in [Ca 2+ ] i during differentiation. This developing spontaneous activity may also be consistent with the observation of spontaneous and burst firing potentials in dopaminergic neurons [42] , [43] , [44] , [45] . Ca 2+ signaling responses have not been studied widely in ESC-derived neuronal cultures before; apart from our previous work, a recent study by Malmersjo and co-workers [46] in human ESC-derived TH + neurons observed the development of Ca2+ responses in those cells (to, for example, KCl, Glut, or neurotensin stimulation) and concluded there were functional similarities to primary ventral midbrain dopaminergic neurons of mice.…”
Section: Discussionsupporting
confidence: 89%
“…The remaining neurons had a much higher basal firing frequency, ranging between 4 and 11 Hz and characterized by mean values of 6.8 ± 1.4 and 6.4 ± 0.5 Hz, when measured with μG-SCD-MEAs and MEAs ( p > 0.1), respectively. This heterogeneity of responses can, most likely, be ascribed to the presence of distinct neuronal populations such as DA neurons from SN, GABAergic and DA neurons from the nearby ventral tegmental area (Berretta et al, 2010; Cucchiaroni et al, 2011). Optical images of GFP-TH + neurons that were cultured on μG-SCD-MEAs are provided in Figure 3D.…”
Section: Resultsmentioning
confidence: 99%